2016
DOI: 10.1021/acs.est.6b00902
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofouling Polyvinylidene Fluoride Membrane Modified by Quaternary Ammonium Compound: Direct Contact-Killing versus Induced Indirect Contact-Killing

Abstract: Widespread applications of membrane technology call for the development of antibiofouling membranes. For the traditional contact-killing strategy, the antibacterial action is restricted to the surface: the membrane loses its antibiofouling efficacy once its surface is completely covered with a fouling layer. However, in this study, polyvinylidene fluoride (PVDF) microfiltration membranes blended with quaternary ammonium compound (QAC) exhibited a surprisingly lasting antimicrobial activity in the vicinity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 56 publications
0
51
0
Order By: Relevance
“…It has been accepted that the interaction of QACs with microorganisms commences with two steps, i.e., adsorption, and alkyl chain penetration (Ismail et al 2010 ; Lambert and Pearson 2000 ; Zhang et al 2015 ). This should be ascribed to the permanently charged polyatomic ions of the structure NR 4 + giving QACs the property to be readily adsorbed on the cell walls (and membranes) that are normally negatively charged (Zhang et al 2016 , 2017 ). Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been accepted that the interaction of QACs with microorganisms commences with two steps, i.e., adsorption, and alkyl chain penetration (Ismail et al 2010 ; Lambert and Pearson 2000 ; Zhang et al 2015 ). This should be ascribed to the permanently charged polyatomic ions of the structure NR 4 + giving QACs the property to be readily adsorbed on the cell walls (and membranes) that are normally negatively charged (Zhang et al 2016 , 2017 ). Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although extensive information on the occurrence and fate of QACs in the aquatic environment has indicated that biomass sorption via ion exchange, ion pairing and/or hydrophobic bonding largely accounts for the removal of QACs in wastewater treatment plants (a low-speed degradation resulting in the accumulation of QACs in waste activated sludge) (Li et al 2014 ; Tezel and Pavlostathis 2015 ; Zhang et al 2015 ), there is limited knowledge on the subsequent microbial behaviors on exposure to different kinds of QACs (e.g., monoalkonium and benzalkonium compounds). Recent evidence indicates that the immobilized QACs on uniform planes (e.g., membranes) could retard microbial growth through contact-killing (Chen et al 2017 ; Zhang et al 2016 ). However, there is no detailed study on the change of cell viability and microbial metabolisms due to the acute response to QAC shock loads in MBRs treating domestic wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…QACs are amphoteric surfactant, playing the dominating role in control of bacterial growth through formation of mixed-micelle aggregates with hydrophobic membrane elements which solubilize the membrane and lysis of the cells. When bacteria come in contact with QAC, the positive QAC group of quaternary ammonium nitrogen can affect bacterial membrane surface charge balance, which causes cells to inactivate and damaged by penetrating into the cell membranes [123]. Mulder et al (2018) reviewed alkylammonium compounds (QAACs) sequestration mechanisms in soil based on physiochemical properties and the mode of action as antimicrobial agent as schematically displayed in Figure 5 [124].…”
Section: Quaternary Ammonium Compounds (Qac)mentioning
confidence: 99%
“…The antibacterial activity of these compounds was studied as early as the 1900s and it was clinically been used by surgeons for sterilization. [7] Foulants adsorbed at the membrane surfaces can be removed by back-flushing and this might be the key reason due to which reports on PVDF [52,85,87,[124][125][126] and PES [127,128] based membranes modified with QACs exhibited good fouling resistance. Being a cationic agent, the mode of action is sequential and similar to that of primary amine derivatives.…”
Section: Aminesmentioning
confidence: 99%